Urban Forest Management in Boyolali Regency for Supporting the Balanced Development of Urban Areas - Markus Ashadi Ardhiantoro; Sapto Hermawan (Aloha International Journal of Health Advancement (AIJHA), 2021)
This study aims to determine urban forest governance in order to support the balance of urban development in Boyolali Regency. Methods This research is a normative legal research. The sources of legal materials used are primary legal materials and secondary legal materials. The technique of collecting legal materials uses document or library studies and interviews. Interviews were conducted by clarifying with the resource persons. The legal material analysis technique uses the syllogism method and the interpretation uses a deductive mindset. The results showed that urban forest management in order to support the balance of urban development in Boyalali Regency was in accordance with Government Regulation Number 63 of 2002 concerning Urban Forests, but in its implementation it had not gone well. The availability of green open space and urban forest in Boyolali Regency has not met the minimum limit mandated by laws and regulations and there are no regulations specifically regulating the implementation of urban forests. The Boyolali Regency Government can follow the example of other regions or countries such as DKI Jakarta, Tangerang City and Kuningan Regency in managing urban forests. Keywords: governance; green open space; urban forest